Pathogenic and saprophytic Leptospira species in water and soils from selected urban sites in Peninsular Malaysia - Benacer, D.; Woh, P.Y.; Mohd Zain, S.N.; Amran, F.; Thong, Kwai Lin (NCBI, 2013)
Leptospira species were studied in water and soils from selected urban sites in Malaysia. A total of 151 water (n=121) and soil (n=30) samples were collected from 12 recreational lakes and wet markets. All samples were filtered and inoculated into semi-solid Ellinghausen and McCullough modified by Johnson and Harris (EMJH) media supplemented with additional 5-fluorouracil. The cultures were then incubated at 30°C and observed under a dark field microscope with intervals of 10 days. A PCR assay targeting the rrs gene was used to confirm the genus Leptospira among the isolates. Subsequently, the pathogenic status of the isolates was determined using primer sets G1/G2 and Sapro1/Sapro2, which target the secY and rrs genes, respectively. The isolates were identified at serogroup level using the microscopic agglutination test (MAT) while their genetic diversity was assessed by pulsed field gel electrophoresis (PFGE). Based on dark field microscopy, 23.1% (28/121) water and 23.3% (7/30) soil cultures were positive for Leptospira spp. Of the 35 positive cultures, only 8 were pure and confirmed as Leptospira genus by PCR assay. Two out of 8 isolates were confirmed as pathogenic, 5 were saprophytic and one was intermediate. These 8 isolates were negative for the 25 reference hyperimmune rabbit sera tested in the MAT. PFGE showed that all 8 of these environmental Leptospira spp. were genetically diverse. In conclusion, the presence of pathogenic Leptospira spp. in the urban Malaysian environment may indicate and highlight the importance of water screening, especially in recreational lakes, in order to minimize any chance of Leptospira infection.